Benefits and costs of cycling infrastructure investment. - (:unkn) unknown (My University, 2012)
The positive development of cycling in Germany is due to the expansion of the cycle route networks. It is absolutely necessary to further modify existing infrastructure for safety and partly also for capacity reasons. This does not only include pavement cycle paths. There is a variety of different solutions available now which allow municipalities to provide good conditions for moving and stationary cycling traffic. Cost-benefit analyses help to use funds purposefully and justify the investments vis-à-vis third parties or decision-makers for budget decisions. (Difu)
Keywords: Individualverkehr; Fahrradverkehr; Infrastruktur; Radwegenetz; Fahrradnutzung; Fahrradbenutzung; Kosten-Nutzen-Rechnung; Finanzierung